UJI ANTI DIARE INFUSA DAUN MIMBA (Azadirachta indica Juss) TERHADAP MENCIT JANTAN GALUR SWISS - Ika Puspitaningrum; Arsa Wahyu N.; Suwarmi - (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
ABSTRACT This study aims to determine the efficacy of neem leaf infusion antidiarrheal (Azadirachta indica Juss.) against male mice strain Swiss, and to determine the effective dose infusion of neem as antidiarrheal. Object of this study was the time of the occurrence, duration of diarrhea, and stool consistency and number of male mice strains Swiss. Samples of fresh neem leaves is used in the preparations made ​​by the infusion technique is random sampling . A 25 of mice was divided into 5 groups consisting of groups I- III were given neem leaf infusion dose of 68.12 mg/kgbw; 204.36 mg/kgbw and 613.08 mg/kgbw, group IV as a positive control group that were given loperamide HCl dose of 0.73 mg/kgbw, and group V as a negative control group that were given 0.75 ml of oleum ricini. All administration is done orally. Observations include the time of occurrence of diarrhea , duration of the course of diarrhea, stool consistency and number of each were evaluated statistically by Anova method and post- ANOVA test . The results showed that Infuse leaves of neem has antidiarrheal efficacy of male mice strain Swiss. Neem leaf infusion at a dose of 204.36 mg/kgbw and 613.08 mg/kgbw have antidiarrheal effects comparable to loperamide HCl dose of 0.73 mg / kgbw.